2023
DOI: 10.1186/s40001-023-01415-w
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance increases the risk of severity and acquisition of COVID-19: a systematic review and meta-analysis

Arman Shafiee,
Kyana Jafarabady,
Shahryar Rajai
et al.

Abstract: Background Understanding the association between sleep quality and COVID-19 outcomes is crucial for effective preventive strategies and patient management. This systematic review aims to evaluate the impact of sleep quality as a risk factor for acquiring COVID-19 infection and the severity of the disease. Methods A comprehensive search of electronic databases was conducted to identify relevant studies published from the inception of the COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Short sleep duration and sleep disturbances have been found to be associated with increased incidence of upper respiratory tract infections, including COVID-19, 8,30,31 as well as poorer outcomes from these infections. 8,31 Our longitudinal analysis extends these findings to show the bidirectional nature of the relationship between sleep and COVID-19 within the same cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short sleep duration and sleep disturbances have been found to be associated with increased incidence of upper respiratory tract infections, including COVID-19, 8,30,31 as well as poorer outcomes from these infections. 8,31 Our longitudinal analysis extends these findings to show the bidirectional nature of the relationship between sleep and COVID-19 within the same cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Short sleep duration and sleep disturbances have been found to be associated with increased incidence of upper respiratory tract infections, including COVID-19, 8,30,31 as well as poorer outcomes from these infections. 8,31 Our longitudinal analysis extends these findings to show the bidirectional nature of the relationship between sleep and COVID-19 within the same cohort. A large cross-sectional study 32 of both community and hospitalised COVID-19 cases has previously shown a bidirectional relationship between insomnia and long COVID, reporting increased risk of long COVID among people with pre-pandemic insomnia and a higher prevalence of post-infection insomnia among people with long COVID.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is a high‐dimensional phenotype, 1 is different for men and women, and is changing with increasing age 2 . Disturbances in single dimensions of habitual sleep are increasingly recognized as important risk factors contributing to the onset of age‐related diseases, including metabolic, cardiovascular and neurodegenerative diseases, 3–7 COVID‐19 and influenza susceptibility, 8,9 some types of cancer, 10–12 and mortality 13 . Mendelian randomization, which uses genetic variants associated with the exposure of interest as instrumental variable, 14–17 indicated that short self‐reported sleep duration and poor sleep quality play a causal role in the risk of cardiometabolic disease and dementia, 16,18–20 and susceptibility to some infectious diseases, 9 thus making sleep of particular interest as target for disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 5 Recently, obstructive sleep apnea (OSA) has been demonstrated in two large studies to be associated with the development of PASC. 6 , 7 Although poor sleep quality and short sleep duration are associated with an increased risk of acute COVID-19 infection, 8 , 9 it is uncertain whether they also are related to a higher likelihood of PASC.…”
Section: Introductionmentioning
confidence: 99%